The association between problematic internet use and social anxiety within adolescents and young adults: a systematic review and meta-analysis - Ding, Haiyang; Cao, Bing; Sun, Qixuan (Frontiers in Public Health, 2023)
Objective Although numerous studies have investigated the association between problematic internet use (PIU) and social anxiety, the findings have no yet reached consistent. The present meta-analysis aims to examine the association between PIU and social anxiety within adolescents and young adults (age range: 14–24 years old). Method The meta-analysis systematically retrieved the studies prior to September 7, 2023 from Web of Science, PubMed, PsycINFO, Scopus, CNKI, and CQVIP. The meta-analysis based on random-effects model to conduct the research. Stata Version 17.0 and JASP 16.3.0 was used to analysis. Results The meta-analysis ultimately included 37 studies (37 effect sizes in total), involving a total of 36,013 subjects. Our findings indicated that the overall correlation between PIU and social anxiety was significant positive [r = 0.333, 95% CI (0.292, 0.373), p < 0.001]. Their association was significantly moderated by publication year, measurement tools for PIU and social anxiety but not significantly by culture context, developmental level and gender. Conclusion This meta-analysis suggests that social anxiety is a predictor of the development of PIU in adolescents and young adults. Furthermore, the study also finds the possibility that contemporary adolescents and youth may exhibit a more “global” behavior pattern, potentially emphasizing fewer differences between cultures, generations and genders.